1991
DOI: 10.1002/macp.1991.021920922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polyamides derived from anhydro‐ and dianhydroalditols

Abstract: The three isomeric 1,4:3,6-dianhydroalditols with D-gluco-(2), D-manno-(11) and L-id0 (17) configuration and both 1,4-anhydroalditoIs with threo (22) and erythro (27) configuration were efficiently transformed into the corresponding diamino derivatives. Interfacial polycondensation of these chiral heterocyclic diamines with purchasable aromatic and aliphatic carboxylic acid chlorides gave polyamides 35 and 36a-f, 37, 38 and 39a-d. The polymers were characterized using IR and 'H/13C NMR spectroscopy. Number-ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 25 publications
1
36
1
Order By: Relevance
“…In the thermograms of polyamide 6a , a glass transition was observed at 160 °C. This T g was much higher than those reported (ranging 50 − 130 °C) for the polyamides obtained by polycondensation of the isohexide‐derived diamines with sebacoyl chloride, indicative of the increased stiffness of the polymer main chain due to the highly rigid 5‐6‐5 fused ring system. The T g of polyamide 6d was high, at 270 °C.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…In the thermograms of polyamide 6a , a glass transition was observed at 160 °C. This T g was much higher than those reported (ranging 50 − 130 °C) for the polyamides obtained by polycondensation of the isohexide‐derived diamines with sebacoyl chloride, indicative of the increased stiffness of the polymer main chain due to the highly rigid 5‐6‐5 fused ring system. The T g of polyamide 6d was high, at 270 °C.…”
Section: Resultscontrasting
confidence: 58%
“…In addition, isohexides have been derived into amino‐functionalized compounds . Among these, diamines have been used as monomers for the preparation of polyamides with several advantageous properties such as high T g 's and semicrystallinity, making them suitable for engineering applications …”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous publications dealing with polymers based on 1 , only a limited number of them are devoted to polyamides. Thiem and Bachmann15 thus carried out the interfacial polycondensation of terephthaloyl or isophthaloyl chlorides with 2,5‐diamino‐1,4:3,6‐dianhydro‐2,5‐dideoxy‐ D ‐sorbitol dihydrochloride to obtain the corresponding polyamides.…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that the use of catalysts like Lewis acids or enzymes is indispensable for successful polycondensations of isosorbide with diacids. Isosorbide is an interesting monomer too for the synthesis of aromatic polyesters, polyamides, polyurethanes and polyethers …”
Section: Introductionmentioning
confidence: 99%